Jawabanmu

2014-07-03T01:10:44+07:00
2+ (x/(2+(x/2+(...))) = p
2 +         x              = p
       2 +     x          
             2 +     x       
                   2 +   x    
                         2 + ...
p - 2 = x/p
p² -  2p = x
p² - 2p - x = 0
P1,2 = 2 +- √(4 + 4x)
                   2
P1,2 = 2 +- √(1 + x) dgn x ≥ 0
Contoh jika x = 0 maka p = 2+1 = 3 atau p = 2-1 = 1
           jika x = 3 maka p = 2+2 = 4 atau p = 2-2 = 0
           jika x = 8 maka p = 2 + 3 = 5 atau p = 2 - 3 = -1 dst